A quantitative characterization of spatial arrangement of air voids in mortars via X-ray CT and numerical calculations. (19th December 2022) - Lyu, Kai; Garboczi, E.J.; Liu, Xiaoyan
Highlights: The spatial arrangement of air voids in mortars was quantitatively evaluated via X-ray CT and numerical calculation from both paste-void proximity and void-void proximity. An improved growing sphere algorithm was proposed to calculated the void spacing based on the paste-void proximity definition. The effect of fine aggregate size and blended proportions on the void spacing distribution was investigated. Abstract: Compared with overall air void content and size distribution, the spatial arrangement of air voids is probably of more importance in the durability of cement-based materials subjected to repeated freeze–thaw cycles. In this paper, a method for computing the three-dimensional distribution of air voids according to the void–void proximity and the paste–void proximity definitions based on X-ray computed tomography (XCT) images is proposed, For better illustration of the method, six mortar samples with varying fine aggregate size and blended proportions were prepared and examined. Characteristic parameters, including average spacing, SF50, SF95, and Gaussian expectation were quantitatively derived from the various distribution curves in various ways, which follow the same trends among the six mortar samples. Then, the Lu and Torquato equations were used to analytically calculate the spacing and compared with the results obtained via numerical calculation, showing good agreement for both paste-void proximity and void-void proximity. Based on the results of this paper and on a previous paper on these same mortars, we propose an alternative method for quantifying the three-dimensional arrangement of air voids with less time and higher accuracy than two-dimensional methods.